The E3 ubiquitin ligase MARCH1 mediates downregulation of plasma membrane GABAB receptors under ischemic conditions by inhibiting fast receptor recycling - Musadiq A. Bhat; Mohammad Hleihil; Irene Mondéjar; Thomas Grampp; Dietmar Benke (Scientific Reports)
Abstract GABAB receptors mediate prolonged inhibition in the brain and are important for keeping neuronal excitation and inhibition in a healthy balance. However, under excitotoxic/ischemic conditions, GABAB receptors are downregulated by dysregulated endocytic trafficking and can no longer counteract the severely enhanced excitation, eventually triggering neuronal death. Recently, we developed interfering peptides targeting protein-protein interactions involved in downregulating the receptors. Treatment with these peptides restored GABAB receptor expression after an ischemic insult and thereby inhibited neuronal overexcitation and progressive neuronal death. In this study, we searched for GABAB receptor interactions that specifically occur under ischemic conditions. We found that the E3 ubiquitin ligase MARCH1 is specifically upregulated under ischemic/excitotoxic conditions. Upregulated MARCH1 interacts with GABAB receptors and triggered downregulation of plasma membrane GABAB receptors by inhibiting fast recycling of the receptors. We developed an interfering peptide that inhibits the MARCH1/GABAB receptor interaction. Treatment of cultured neurons subjected to ischemic stress with this peptide restored receptor expression and as a consequence stopped progressive neuronal death. Thus, inhibiting the interaction of GABAB receptors with MARCH1 to restore cell surface receptor expression might be a promising strategy to prevent progressive neuronal death induced by ischemic conditions.